Islamic Ethical Thought of Nasruddin Thusi - Utari Prima Ningrum (Dirosatuna: Journal of Islamic Studies, 2019)
Abstract: This paper aims to discuss the thoughts Nashiruddin Ath-Thusi especially his thoughts on Islamic ethics. Ethics or what is often referred to as morality is a behavior or habit done by humans in their daily lives. This ethic is related to right and wrong actions, both good and bad, which are carried out by humans, which should be sourced from the Qur’an and As-Sunnah. As we know the current generation has begun to decrease to pay attention to good ethics or morals in everyday life. Ethics is usually also interpreted as teachings or assumptions about character that discusses values as a measure of an action or act that can be called good or bad. In this paper also discusses how Ath-Thusi life and some of his work. Not only that this writing also discusses some thoughts of Ath-Thusi such as the politics, of the soul, and the household. Keywords: Nasruddin Thusi, Islamic Ethic, Thought.